O renascer da pós-graduação em poéticas visuais na UNESP, campus de Bauru: contribuição valiosa para os cursos de artes - Palhaci, Maria do Carmo Jampaulo Plácido [UNESP]; Nicola, Ricardo Luis [UNESP]; Simões, Rosa Maria Araújo [UNESP] (My University, 2011)
The postgraduation program in Visual Poetics, Master level, to be started in 2011 at the faculty of Architecture, Arts and Communication of the state university of São Paulo "Julio de Mesquita Filho"- Bauru Campus, arises strong and well structured contributing to the strengthening of Arts courses. It is noteworthy that the Visual Poetics area has graduated in its previously existing program, more than 30 (Thirty) masters and 8 (eight) doctors. They are currently linked to state and federal universities of Sao Paulo, Parana, Santa Catarina and Mato Grosso do Sul . Ricardo Nicola is Post-Doctor by IES since 2007: University of Toronto, Canada, is presented as mentor and coordinator of the renaissance process of masters program in Visual Poetics.Nelyse Apparecida Malro Salzedas , graduated as a Professor in 1993 at the same University, she has contributed significantly to the Program implementation and will be vice-coordinator of the project.
Keywords: Visual poetry; Visuais; Arts; Masters' degree